Nephro-oncology: a link in evolution. (14th September 2015) - Lacava, Viviana; Coppolino, Giuseppe; Puntorieri, Elvira; Cernaro, Valeria; Lupica, Rosaria; Visconti, Luca; Buemi, Antoine; Santoro, Domenico; Buemi, Michele
Abstract: A multidisciplinary approach represents the best method to interact with patients. Neoplastic and renal diseases are closely related to each other because of an increased risk of cancer among individuals with end-stage renal disease and because of the high prevalence of renal failure in cancer patients. Physicians should be able to know how to prevent and treat the possible complications which may appear during the course of neoplastic disease that may lead to kidney damage such as the Acute Tumor Lysis Syndrome, disorders of hydroelectrolitic balance, metabolic alterations in the calcium-phosphorus, anemia, interstitial and glomerular impairment due to chemotherapy. It is very important to know patients' renal function and directly monitor it, before and during treatment, using formulas for estimating glomerular filtration rate (GFR) and above all, specific biomarkers are more early and sensitive than the increase of creatinine, like neutrophil gelatinase-associated lipocalin. Additionally, physician should consider that alteration of GFR or substitutive renal treatments severely influence dosage of tumor markers and it could lead to wrong diagnosis of cancer. The aim of this article is to provide a review of problems related to cancer relevant in the development of renal failure and try to define the best therapeutic strategies to cope with possible kidney imbalances induced by cancer or its treatment.